Advanced Numerical Techniques for Strength Prediction of Adhesive Joints under Peel Loadings - Lopes, J. P. M.; Campilho, R. D. S. G.; Rocha, R. J. B.; Sanchez-Arce, I. J. (Research Developments in Science and Technology Vol. 7, 2022)
Adhesive bonding is being increasingly used for structural applications on account of attractive characteristics such as more uniform stress distributions and easiness to joint different materials. A wide variety of joints architectures is available, although the most common are single-lap joints (SLJ), double-lap joints, and scarf joints. T-joints find application in aircraft to bond stiffeners to skin and in the cars between the B-pillar and the rocker, but these are seldom studied in the literature. Different predictive methods are available in the literature for these joints, but some of these only work for specific joint types. This work numerically evaluates, by cohesive zone modelling (CZM), the performance of the structural adhesive Araldite® 2015 in an aluminium T-joint, after CZM validation with experimental results using a similar geometry, which enabled to use this technique in the subsequent numerical study. A purely CZM numerically study is then carried out to capture the behaviour of different T-joints geometrical configurations when subjected to peel loads. The work includes a parametric study, considering stress analysis in the elastic loading stage and maximum load (Pm) prediction, considering four geometrical parameters: flat adherend thickness (a), T-element thickness (t), overlap length (l) and T-element radius (r). A significant effect on Pm was found for the tested parameters, and the CZM method revealed to be a precise method for studying T joints with precision and accuracy.